OTONOMI DESA ADAT: SEBUAH FATAMORGANA? KASUS DARI DESA ADAT INTARAN, BALI, INDONESIA - Rahmatunnisa, Mudiyati; Ramaditya, Fauzan; Putra, Haelvyn Pratagrahana; Khairunnisa, Anandya (Jurnal Academia Praja, 2023)
This study examines the empirical experience of indigenous village autonomy in Indonesia as normatively regulated in the 1945 Constitution and the recent 2014 Law on Regional Government. The prolonged debate by many on the issue has mainly focused on how autonomous indigenous villages have actually been due to various forms of state intervention (also referred to as "stateization"). This study specifically identifies a number of empirical practices of autonomy in the Desa Adat Intaran of Bali Province. The case study provides a fertile ground for a variety of information related to the subject matter amidst the recent developments in the COVID-19 pandemic recovery efforts and the strong resistance of village communities to the LNG Terminal development project on Mertasari Beach by the Central Government and Bali Province in 2022 within the territory of Desa Adat Intaran. This study is particularly important in terms of adding current data and information to the current debate on the practice of indigenous village autonomy in Indonesia. This research utilizes qualitative research methods with a series of interviews, Focus Group Discussions as well as literature studies as data collection techniques. Triangulation techniques were also used to validate the qualitative data. The study argues that there has been noticeable state intervention in the implementation of autonomy of Desa Adat Intaran both in terms of institutions, programs and the allocated village budget. This finding confirms that there is a large gap between normative indigenous village autonomy and actual practice.